2003
DOI: 10.1074/jbc.m300711200
|View full text |Cite
|
Sign up to set email alerts
|

CD40-dependent Activation of Phosphatidylinositol 3-Kinase/Akt Pathway Mediates Endothelial Cell Survival and in Vitro Angiogenesis

Abstract: CD40 has been involved in tumor and inflammatory neoangiogenesis. In this study we determined that stimulation of endothelial CD40 with sCD154 induced resistance to apoptosis and in vitro vessel-like formation by human microvascular endothelial cells (HMEC). These effects were determined to be mediated by CD40-dependent signaling because they were inhibited by a soluble CD40-muIg fusion protein. Moreover, apoptosis of HMEC was associated with an impairment of Akt phosphorylation, which was restored by stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 50 publications
3
79
4
Order By: Relevance
“…It has been demonstrated that cAMP causes PI3K-dependent Akt activation in hepatocytes and hepatic WIF-B9 cells, probably in a PKA-dependent manner (Li et al, 2000;Kagawa et al, 2002). The PI3K/Akt signaling pathway can be induced by VEGF (Kosmidou et al, 2001;Laughner et al, 2001) and sphingosine 1-phosphate (Morales-Ruiz et al, 2001) and plays a central role in angiogenesis by promoting endothelial sprouting, proliferation, migration, and vessel-like structure formation (Deregibus et al, 2003;Licht et al, 2003). These evidences suggest that many angiogenic factors activate the PI3K/Akt signaling pathway, which is a central mediator of angiogenesis (Zachary, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cAMP causes PI3K-dependent Akt activation in hepatocytes and hepatic WIF-B9 cells, probably in a PKA-dependent manner (Li et al, 2000;Kagawa et al, 2002). The PI3K/Akt signaling pathway can be induced by VEGF (Kosmidou et al, 2001;Laughner et al, 2001) and sphingosine 1-phosphate (Morales-Ruiz et al, 2001) and plays a central role in angiogenesis by promoting endothelial sprouting, proliferation, migration, and vessel-like structure formation (Deregibus et al, 2003;Licht et al, 2003). These evidences suggest that many angiogenic factors activate the PI3K/Akt signaling pathway, which is a central mediator of angiogenesis (Zachary, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells were characterized as endothelial cells by morphology and positive staining for von Willebrand factor antigen and for CD31, CD105, and the fucosylated receptors for plant lectins (Ulex europeus I and Bandeira simplicifolia). Cytoplasmic staining was positive for vimentin and negative for cytokeratin and desmin, as previously described (17). A previously characterized renal carcinoma cell line (K1) was used as positive control for Pax2 expression (18).…”
Section: Methodsmentioning
confidence: 99%
“…Migration tracks were generated by marking the positions of the nuclei of individual cells on each image. The net migratory speed (velocity straight line) was calculated by the MicroImage software based on the straight line distance between the starting and ending points divided by the time of observation (17). Migration of at least 30 cells was analyzed for each experimental condition.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest the possibility that the inhibition of neoangiogenesis in vivo may be associated with the antitumor synergy of irinotecan and MSC. Endothelial CD40 affects several steps important for angiogenesis, including cell proliferation, motility, and formation of vessel-like structures, through the PI3K/Akt signaling pathway Deregibus et al, 2003), suggesting that Akt mediates angiogenesis. To confirm whether the inhibition of SN-38-induced angiogenesis involves Akt inactivation, we examined the effect of MSC on SN-38-induced Akt expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%